Practical utility of quantitative CSF dynamics in type I Chiari malformation and syringomyelia. Report of 5 cases.: https://doi.org/10.59156/revista.v37i02.520 - Mezzadri, Juan Jose; Miñarro, Diego (Revista Argentina de Neurocirugía, 2023)
Background: the treatment of Chiari malformation I (CMI) and/or syringomyelia (SM) is controversial. The quantitative dynamics of CSF at the craniospinal level is an alternative that could guide therapy. The objective of this publication is to describe 5 cases in which the use of CSF dynamics allowed guiding the treatment.Material: the medical records of 5 cases (mean age: 39 years / 3 women and 2 men) were reviewed. All were studied with MRI in phase contrast. The diagnosis was CMI (1 case) and SM (3 cases) or only SM (1 case). Only 2 cases with CMI+SM underwent surgery (decompression + duraplasty). All were followed between 1.5 and 6 years.Results: case 1 (CMI) the velocity of the CSF was normal, so his headache was treated medically with good results; case 2 (CMI+SM) the velocity was increased so it was intervened controlling the symptoms and the SM; case 3 (CMI +SM) the velocity was normal, its diagnosis being compatible with post-syringomyelic syndrome; case 4 (SM) the velocity was increased at the C5-C6 level, its diagnosis being compatible with a primary spinal SM; case 5 (CMI + SM) after the intervention it was observed that the velocities and the SM took 16 months to normalize.Conclusion: In the cases described, the CSF dynamics allowed the correct diagnosis to be made, to determine the advisability of performing surgery, to find the cause and to control the postoperative evolution.
Keywords: Chiari I malformation; CSF dynamics; phase contrast MRI; post-syringomyelic syndrome; primary spinal syringomyelia; syringomyelia